2022
DOI: 10.1007/s12015-022-10470-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis

Abstract: In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The shift in interest was promoted by research studies increasingly implying that the therapeutic effect of stem cells is mediated by the extracellular paracrine factors exerted via EVs [38]. Many research studies have demonstrated the successful utility of AFSC-EVs in pre-clinical models to treat different pathologies including necrotizing enterocolitis [51,52,100,101], hypoplastic neonatal lungs [65,116,117] and wound healing [104,105]. AF composition is dynamic and often represents the gestation-dependent development of fetal organs [118,119].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shift in interest was promoted by research studies increasingly implying that the therapeutic effect of stem cells is mediated by the extracellular paracrine factors exerted via EVs [38]. Many research studies have demonstrated the successful utility of AFSC-EVs in pre-clinical models to treat different pathologies including necrotizing enterocolitis [51,52,100,101], hypoplastic neonatal lungs [65,116,117] and wound healing [104,105]. AF composition is dynamic and often represents the gestation-dependent development of fetal organs [118,119].…”
Section: Discussionmentioning
confidence: 99%
“…As a cell-free product loaded with bioactive molecules, they contain many desirable properties. EVs have been shown to modulate inflammation [58,[100][101][102], curb oxidative stress [103] and augment wound healing [104,105], ultimately leading to tissue regeneration. Moreover, as a natural cell-derived product, EVs present advantages such as biocompatibility and minimal toxicity for recipients.…”
Section: Therapeutic Applications Of Af-evs and Afsc-evsmentioning
confidence: 99%
“…Despite a lack of complete understanding of the mechanism of NEC pathogenesis, the microbiome and the understanding of its role in NEC development has led to the microbiome being a possible area of interest for prevention and treatment [68]. The means of altering the microbiome in beneficial ways which have been shown to decrease the incidence of NEC and thus may prevent NEC include breastfeeding, antibiotic stewardship, and the use of probiotics [9,[68][69][70][71]. However, there is still risk associated with the use of probiotics due to the immature immune systems of preterm infants.…”
Section: Prevention and Therapymentioning
confidence: 99%
“…McCulloh et al concluded that exosomes derived from SCs were not significantly different from SCs when treating NEC mice and significantly reduced NEC incidence and severity [ 138 , 139 ]. In vitro, exosomes derived from human breast milk SCs (HBM-exos) preferentially inhibited the inflammatory response of intestinal epithelial cells, whereas exosomes from hAFSCs (AFSC-exos) preferentially regulated the migration of intestinal epithelial cells; in vivo, the number of ileal crypts recovered faster after intervention with HBM-exos ( Figure 15 ) [ 140 ]. BM-MSCs produce a variety of soluble mediators, such as cytokines, growth factors, microRNAs, and exosomes, to mitigate NEC-related injury [ 141 ].…”
Section: Application Of Scs In Refractory Diseases Of Newbornsmentioning
confidence: 99%
“… Comparison of the effects of AFSC-exo and HBM-exo interventions in mouse models of NEC. Both exosomes reduce NEC-related intestinal damage, significantly reduce NEC scores, and reduce systemic and ileal inflammation and NEC-related brain damage [ 140 ]. …”
Section: Figurementioning
confidence: 99%